2019
DOI: 10.1007/s10967-019-06992-x
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Lab-on-a-Chip analytical systems for nuclear applications: optical performance and UV–Vis–IR material characterization after chemical exposure and gamma irradiation

Abstract: The use of microfluidics technology and the miniaturization of analytical techniques is of high interest for the chemical and nuclear industries. In the latter, the reduction of effluents deriving from actinides concentration monitoring along R&D and pilot-scale purification processes is a permanent concern. lndeed, the extremely harsh operation conditions limit the imple mentation of standard analytical techniques and methodologies, and in this regard, the use of spectrophotometric techniques for effluents ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Many common chip materials on the market are compatible with the chemical system of interest here, but the real challenge is verifying if the chip material will allow for optical interrogation. Several chip materials and designs have been developed and tested with UV–vis absorption techniques, and it is found that by using reference spectra, correction problems are minimized. , …”
Section: Resultsmentioning
confidence: 99%
“…Many common chip materials on the market are compatible with the chemical system of interest here, but the real challenge is verifying if the chip material will allow for optical interrogation. Several chip materials and designs have been developed and tested with UV–vis absorption techniques, and it is found that by using reference spectra, correction problems are minimized. , …”
Section: Resultsmentioning
confidence: 99%
“…It is described in great detail in Rodríguez-Ruiz et al 25,26 and can be made in different materials. 15 For uranium experiments, a polydimethylsiloxane (PDMS; Sylgard 184 elastomer kit, supplied by Dow Corning) chip was selected. For more details on the process of chip manufacturing by casting, the reader can refer to Rodríguez-Ruiz et al 26,27 For plutonium, the analyses were performed in a glove box.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we investigated the chemical and radiation resistance of these materials in more detail and compared their optical performance using microsystems fabricated in different materials, based on the analysis of lanthanides. 15 In this study, the evaluation of a complete optofluidic analytical approach, potentially combining both UV-Vis and Raman detection schemes, and suitable to be operated in a confined enclosure, such a glove box, will be carried out for the analysis of uranium (IV), uranium (VI), and plutonium (IV) pure solutions and mixtures, with the aim of subsequently developing microfluidic analytical systems resulting in the detection of actinides using both spectrophotometric techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed a glass LoC with three sensing microchannels of different optical path lengths (L = 1.5, 3.5 and 15 mm respectively), with width 650 µm and depth 250 µm, see Figure 1 and Figure 2). Glass was chosen, over PDMS for instance [12], because of its optical and mechanical properties regarding, notably, chemical exposure and irradiation [43]. This monolithically integrated device was manufactured by FEMTOPRINT® following our specifications, with an innovative femtosecond laser pulses micromachining technology for ultra-fast micromolding of fused silica.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%